INTERCULTURAL COMMUNICATION BETWEEN INDIGENOUS PEOPLE AND MIGRANTS IN BUILDING TOLERANCE IN ASAHAN REGION - Suwardi Lubis; Rizabuana; Riko Andika Rahmat Pohan (IPMI Publisher, 2025)
This study explores intercultural communication between migrant communities and indigenous populations in Asahan, North Sumatra Province. The research adopts a qualitative methodology utilizing Symbolic Interaction and Uncertainty and Anxiety Management theories. The primary objective is to understand and analyze intercultural communication between indigenous people and migrants in fostering tolerance in Asahan. Employing a qualitative approach, the research emphasizes meaning over generalization. It elucidates how intercultural communication contributes to tolerance-building among residents. Findings indicate that effective communication exists between migrants and the indigenous Asahan community, despite initial uncertainty and anxiety among migrants, as Asahan is reputed for its tolerance, and its people are notably welcoming to newcomers. Symbolic interactions give rise to new meanings and social structures, aligning with the essence of symbolic interaction theory, which posits that meaning and social structure are created and maintained through social interaction. Intercultural communication occurs daily in activities such as shopping, taking children to school, and hosting events. The intended outcome of this research is a publication in a reputable international journal.